2007
DOI: 10.1038/sj.ijo.0803667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of food form on appetite and energy intake in lean and obese young adults

Abstract: Objective: To investigate the independent effect of food form on appetite and energy intake in lean and obese adults using high carbohydrate, fat or protein food stimuli. Design: Crossover dietary challenge with matched beverage and solid food forms: high carbohydrate (watermelon and watermelon juice); high protein (cheese and milk); high fat (coconut meat and coconut milk). Results: Regardless of the predominant energy source, the beverage food form elicited a weaker compensatory dietary response than the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
231
2
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(250 citation statements)
references
References 53 publications
8
231
2
9
Order By: Relevance
“…3,15,16 Whole apples have been reported to be more satiating than apple juice, 17 and watermelon, cheese or coconut, providing greater compensation than isocaloric drinks of watermelon juice, milk or coconut milk in lean and obese adults. 7 In a longer-term study, energy intake was lower in subjects after 4 weeks of consuming jelly beans than soda, supporting the view that liquid foods lead to a positive energy balance. 3 Thus, it is clear that the hypothesis that energy consumed from solid foods evokes a greater satiety response and suppresses energy intake at a subsequent meal compared with liquid foods is unresolved.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…3,15,16 Whole apples have been reported to be more satiating than apple juice, 17 and watermelon, cheese or coconut, providing greater compensation than isocaloric drinks of watermelon juice, milk or coconut milk in lean and obese adults. 7 In a longer-term study, energy intake was lower in subjects after 4 weeks of consuming jelly beans than soda, supporting the view that liquid foods lead to a positive energy balance. 3 Thus, it is clear that the hypothesis that energy consumed from solid foods evokes a greater satiety response and suppresses energy intake at a subsequent meal compared with liquid foods is unresolved.…”
Section: Introductionsupporting
confidence: 52%
“…1,2 Some epidemiological and experimental studies have provided evidence that obesity may be due to the consumption of caloric beverages, because, compared with solid foods, they have been reported to not suppress appetite [3][4][5] and consequently not promote a positive energy balance. 4,6,7 However, other experimental studies provide no link between energy intake from liquids and body weight change or FI. 8,9 Many studies have found that solid and liquid forms of the same foods lead to similar FI.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for reduced dietary compensation when energy is consumed in liquid as opposed to solid form (48) and at meals following consumption of caloric beverages (49) , resulting in higher absolute energy intakes among those consuming SSB. These beverage products are energy-dense yet nutrient-poor Table 3 Effect of change in SSB intake from ages 10 to 13 years on WC at age 13 years adjusted for total adiposity (n 2455)*, Avon …”
Section: Discussionmentioning
confidence: 99%
“…For example, people do not sufficiently reduce energy intake in response to calories ingested from SSBs. 78,79 Also well known is the biological relationship underpinning energy balanceFa change in one side of the equation will result in a response on the other side of the equationFas the body works to maintain a steady state. Yet, there remain many unanswered questions in this area.…”
Section: Discussionmentioning
confidence: 99%